Bentuk Ligulate Extension Beberapa Jenis Kayu - Andi D. Yunianti; I Ketut N. Pandit (Jurnal Ilmu dan Teknologi Kayu Tropis, 2010)
The key difference between hardwood and softwood is lies on the presence of the vessel element on the hardwood and its absence on the softwood. Many researches have been done especially focused on vessel’s shape, volume, forms as well as on pit of vessel. However, few of those research focused on the vessel’s ligulate extensions. This research was study the shape of ligulate extensions on acacia, teak, gmelina, and sungkai woods to examine samples from maceration. The results revealed that ligulate extension shapes were diverse within one wood species. Furthermore, wood samples that coming from same part are still varied in its ligulate extension. Therefore, shapes of ligulate extension are unrecommended as a mean of wood identification. It is presume the variation of ligulate extension is highly related to the vessel functions as a food transporter, mechanical function as well as the presence of earlywood and latewood.